Chronic Atrophic Gastritis Presenting as Hemolytic Anemia due to Severe Vitamin B12 Deficiency - Amanda M. Woodford; Rabhea Chaudhry; Gabriella A. Conte; Varsha Gupta; Madhurima Anne (Case Reports in Hematology)
Vitamin B12 is an essential nutrient which plays an important role in neurological function, hematopoiesis, and DNA synthesis. Low levels usually stem from either poor intake or a malabsorptive process. Presently, the most common cause of vitamin B12 deficiency is food-bound cobalamin malabsorption, which occurs when there is impaired release of vitamin B12 from ingested food due to an outstanding factor preventing the release of the nutrient from its transport protein. Such causes include achlorhydria, gastritis, gastrectomy, or the use of PPIs or antacids. A rarer cause is autoimmune chronic atrophic gastritis, resulting in pernicious anemia. In this disease process, there is destruction of parietal cells and thus a reduction in intrinsic factor, which is essential to the absorption of vitamin B12. Deficiency will result in a variety of abnormalities including but not limited to pancytopenia, paresthesias, and neuropsychiatric symptoms. A rare manifestation of vitamin B12 deficiency is hemolytic anemia, which occurs due to intramedullary and extramedullary dysfunction. This case describes a 46-year-old male with no past medical history who presented with chest pain, fatigue, and progressive weakness, found to have hemolytic anemia, ultimately attributed to vitamin B12 deficiency. Antiparietal cell antibodies and intrinsic factor antibodies (IFA) were both negative. Still, the patient underwent an endoscopy with biopsies of the stomach; pathology was consistent with chronic metaplastic atrophic gastritis. The patient improved with intramuscular vitamin B12 supplementation. This case highlights both a rare cause and presentation of vitamin B12 deficiency. Patients with autoimmune chronic atrophic gastritis should have antiparietal cell or intrinsic factor antibodies. Still, seronegative patients have been reported, like this patient. Additionally, hemolytic anemia secondary to vitamin B12 deficiency is uncommon. The presentation will usually mirror that of a thrombotic microangiopathy (TMA), including hemolytic anemia with schistocytes on peripheral blood smear and thrombocytopenia, as it did in this patient. This clinical entity is described as pseudothrombotic microangiopathy and is crucial to identify in order to prevent the initiation of invasive treatment strategies such as plasmapheresis.